Max Aub, Campo de los almendros. Ed. de Francisco Caudet. Castalia, Madrid, 2000; 787 pp. - Rojo Leyva, Gabriel (Nueva Revista de Filología Hispánica (NRFH), 2002)
Se reseñó el libro: Campo de los almendros.